Menguatkan Hak Masyarakat Adat Atas Hutan Adat (Studi Putusan MK Nomor 35/ PUU-X/2012) - Faiq Tobroni (The Constitutional Court of the Republic of Indonesia, 2013)
If the Government is always consistent to ensure the rights of indigenous people over ulayat forest, of course there will be no legislation which is contrary to the constitution, because the constitution had always guaranteed it. The Decision of Constitutional Court Number 35/PUU-X/2012 which declares that Article 1 point 6, Article 4 paragraph (3), article 5 paragraph (1), paragraph (2), paragraph (3) of Law 41/1999 on Forestry unconstitutional shows that there is inconsistency in regulating indigenous forest. In the perspective of human rights, the articles have a spirit of protection of indigenous peoples’ rights over ulayat forest which is repressive derogable in nature. Meanwhile, the Constitutional Court decision has the spirit of progressive derogable protection. The first spirit means that because the state could derogate the recognition of ulayat forest if it is incompatible with the development of society and contrary to the principles of the Unitary State of the Republic of Indonesia, then the ulayat forest should be seen as the state forest. In the contrary, the next spirit means that although the state could derogate the recognition based on the preceeding requirements, the ulayat forest should be defined as ulayat forests. The first spirit is a repressive one because it aims at subordinating ulayat forests in the name of state forests. Meanwhile, the progressive spirit has the character of liberation and empowerment, it aims at removing the term of ulayat forests from state forests.